Scoping review of resin cements modified by antimicrobial agents: Effects of incorporation (Research, Society and Development, 2024)
The purpose of this scoping review was to assess the modification effects of resin cements on antimicrobial capacity, mechanical properties, and conversion degree. Researches in the Embase, PubMed, SCOPUS, Cochrane library and Web of Science databases were enriched with manual searches, between May and June 2020, using the keywords “antibacterial resin cement” NOT “adhesive” NOT “ionomer”. The criteria included articles written in English, in vitro studies assessing resin cements with the incorporation of antimicrobial agents, describing conversion degree and/or mechanical properties, and/or effect of the antimicrobial agents, and articles indexed in the Journal Citation Reports (JCR) database. A total of 100 articles were found, of which 11 were selected by title and/or abstract, according to the inclusion criteria. From the 7 articles selected for full reading, 3 articles remained in this scoping review. These had high variability in materials and methods, making it difficult to perform the data statistical analysis; thus, a descriptive analysis was performed. There is a need for a resinous adhesive cementing agent with antimicrobial action since the bacteria infiltration at the adhesive interface is directly related to secondary dental caries with reduced longevity and survival of prosthetic treatments.